2021
DOI: 10.2147/dddt.s295825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spray Drying Conditions on Physical Properties of Panax notoginseng Saponin (PNS) Powder and the Intra-Batch Dissolution Variability of PNS Hydrophilic Matrix Tablet

Abstract: Purpose: Understanding raw material variability and its impact on product quality are crucial for developing robust pharmaceutical processes. This work aimed to study the effects of spray drying conditions on properties of the spray dried Panax notoginseng saponin (PNS) powders as well as the subsequent intra-batch dissolution variability of PNS hydrophilic matrix tablets. Methods: The Plackett-Burman design was applied to screen the critical process parameters (CPPs). Then, the Box-Behnken design was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The water content in this solution was calculated to be 4.65 tonnes. Commercially, spray dryers can make products with a 3–4% moisture content. Consequently, a moisture content of 3% was used as an estimate in this study. To achieve this moisture content, 4.62 tonnes of water would have to evaporate from an initial water content of 4.65 tonnes in the feed solution.…”
Section: Resultsmentioning
confidence: 99%
“…The water content in this solution was calculated to be 4.65 tonnes. Commercially, spray dryers can make products with a 3–4% moisture content. Consequently, a moisture content of 3% was used as an estimate in this study. To achieve this moisture content, 4.62 tonnes of water would have to evaporate from an initial water content of 4.65 tonnes in the feed solution.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, water-soluble excipients present in matrix tablets dissolve earlier and micro-channels are developed, which increase water penetration into the core of the matrix and increase the dissolution rate. A number of studies have reported an increase in the dissolution rate by increasing the quantity of lactose (a water-soluble excipient) in the matrix tablets [ 12 ], and a decrease in the dissolution rate with the inclusion of di-basic calcium phosphate (a water-insoluble excipient) [ 13 ]. Changes in the GIT conditions can also affect the mechanism of the dissolution rate due to enzymatic activity and variation in pH of the medium from highly acidic to alkaline.…”
Section: Introductionmentioning
confidence: 99%